Analytical characterization of secondary phases and void distributions in an ultrafine-grained ODS Fe-14Cr model alloy - de Castro, V; Leguey, T; Auger, M; Lozano-Perez, S; Jenkins, M (2011)
Two model Fe-14Cr alloys, one containing 0.3 wt.% of Y2O 3 particles, were fabricated by mechanical alloying of Fe and Cr elemental powders under a He atmosphere. They were subsequently consolidated and thermomechanically treated to produce ultra-fine grained materials. Cr-carbides and oxides were found in both alloys. The oxide dispersion-strengthened (ODS) alloy also contained a fine dispersion of nanoparticles, some of them having a Y-O rich core and a Cr-rich shell. Nanometric sized voids were found in both materials, often attached to secondary phases, dislocations and grain boundaries. Their sizes were significantly smaller in the ODS alloy. © 2010 Elsevier B.V. All rights reserved.